2018
DOI: 10.1063/1.5027243
|View full text |Cite
|
Sign up to set email alerts
|

Improving low-accuracy protein structures using enhanced sampling techniques

Abstract: In this paper, we report results of using enhanced sampling and blind selection techniques for high-accuracy protein structural refinement. By combining a parallel continuous simulated tempering (PCST) method, previously developed by Zang [J. Chem. Phys., 044113 (2014)], and the structure based model (SBM) as restraints, we refined 23 targets (18 from the refinement category of the CASP10 and 5 from that of CASP12). We also designed a novel model selection method to blindly select high-quality models from very… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…In actual blacksmithing, repeated heating and cooling of the sample is an important aspect. A natural extension of the current protocol would be to combine PC-guided mechanical deformations with continuous simulated tempering, which performs a guided random walk in temperature space (45,46). One might also consider performing Hamiltonian replica exchange simulations with replicas that have different strengths of the side-chain rotamer isomerization barriers to harness the speedup allowed by lowering the barriers without sacrificing the structural specificity attained when using the full barrier heights.…”
Section: Discussionmentioning
confidence: 99%
“…In actual blacksmithing, repeated heating and cooling of the sample is an important aspect. A natural extension of the current protocol would be to combine PC-guided mechanical deformations with continuous simulated tempering, which performs a guided random walk in temperature space (45,46). One might also consider performing Hamiltonian replica exchange simulations with replicas that have different strengths of the side-chain rotamer isomerization barriers to harness the speedup allowed by lowering the barriers without sacrificing the structural specificity attained when using the full barrier heights.…”
Section: Discussionmentioning
confidence: 99%
“…4–8 Å) and there are no other atoms between them, we consider this atom pairs are considered as contacts. The details can be found in our previous PCST‐SBM paper …”
Section: Methodsmentioning
confidence: 99%
“…In our previous paper, in order to improve the low‐accuracy protein structural models, the parallel continuous simulated tempering (PCST) was combined with a temperature‐dependent restraint using structure‐based model (SBM) . In fully solvated molecular dynamics simulation for refinement, it was shown that PCST‐SBM method was able to achieve a more thorough sampling in the configurational space.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations